Head-to-head comparison of certolizumab pegol versus adalimumab in rheumatoid arthritis: 2-year efficacy and safety results from the randomised EXXELERATE study. Issue 10061 (3rd December 2016) - Smolen, Josef S; Burmester, Gerd-Rüdiger; Combe, Bernard; Curtis, Jeffrey R; Hall, Stephen; Haraoui, Boulos; van Vollenhoven, Ronald; Cioffi, Christopher; Ecoffet, Cécile; Gervitz, Leon; Ionescu, Lucian; Peterson, Luke; et al.
Summary: Background: To date, head-to-head trials comparing the efficacy and safety of biological disease-modifying antirheumatic drugs within the same class, including TNF inhibitors, in patients with active rheumatoid arthritis despite methotrexate therapy are lacking. We aimed to compare the efficacy and safety of two different TNF inhibitors and to assess the efficacy and safety of switching to the other TNF inhibitor without a washout period after insufficient primary response to the first TNF inhibitor at week 12. Methods: In this 104-week, randomised, single-blind (double-blind until week 12 and investigator blind thereafter), parallel-group, head-to-head superiority study (EXXELERATE), eligible patients from 151 centres worldwide were aged 18 years or older with a diagnosis of rheumatoid arthritis at screening, as defined by the 2010 ACR/EULAR criteria, and had prognostic factors for severe disease progression, including a positive rheumatoid factor, or anti-cyclic citrullinated peptide antibody result, or both. Participants were randomly assigned (1:1) via an interactive voice and web response system with no stratification to receive certolizumab pegol plus methotrexate or adalimumab plus methotrexate. All study staff were kept masked throughout the study and participants were masked until week 12. At week 12, patients were classified as responders (by either achieving low disease activity [LDA] according to Disease Activity Score 28-erythrocyte sedimentation rate [DAS28-ESR] ≤3·2 or DAS28-ESR reduction ≥1·2 from baseline) or as non-responders. Non-responders to the first TNF inhibitor to which they were randomised were switched to the other TNF inhibitor with no washout period. Primary endpoints were the percentage of patients achieving a 20% improvement according to the American College of Rheumatology criteria (ACR20) at week 12 and LDA at week 104 (week 12 non-responders were considered LDA non-responders). This study is registered withClinicalTrials.gov, numberNCT01500278 . Findings: Between Dec 14, 2011, and Nov 11, 2013, 1488 patients were screened of whom 915 were randomly assigned; 457 to certolizumab pegol plus methotrexate and 458 to adalimumab plus methotrexate. No statistically significant difference was observed in ACR20 response at week 12 (314 [69%] of 454 patients and 324 [71%] of 454 patients; odds ratio [OR] 0·90 [95% CI 0·67–1·20]; p=0·467) or DAS28-ESR LDA at week 104 (161 [35%] of 454 patients and 152 [33%] of 454 patients; OR 1·09 [0·82–1·45]; p=0·532) between certolizumab pegol plus methotrexate and adalimumab plus methotrexate, respectively. At week 12, 65 non-responders to certolizumab pegol were switched to adalimumab and 57 non-responders to adalimumab were switched to certolizumab pegol; 33 (58%) of 57 patients switching to certolizumab pegol and 40 (62%) of 65 patients switching to adalimumab responded 12 weeks later by achieving LDA or a DAS28-ESR reduction 1·2 or greater. 389 [75%] of 516 patients who received certolizumab pegol plus methotrexate and 386 [74%] of 523 patients who received adalimumab plus methotrexate reported treatment-emergent adverse events. Three deaths (1%) occurred in each group. No serious infection events were reported in the 70-day period after treatment switch. Interpretation: These results show that certolizumab pegol plus methotrexate is not superior to adalimumab plus methotrexate. The data also show the clinical benefit and safety of switching to a second TNF inhibitor without a washout period after primary failure to a first TNF inhibitor. Funding: UCB Pharma.